Korelasi teknik pelaksanaan Inisiasi Menyusu Dini (IMD) dengan kejadian perdarahan post partum - Suprapti Suprapti (Politeknik Negeri Jember, 2018)
Early breastfeeding is an initial activity in providing breast milk to babies which have the advantage on the health of your baby's growth and development and fostering ties of affection between mother and baby. Early breastfeeding is also an effort to increase the contractions of the uterus that can reduce the occurrence of bleeding. The purpose of this study is to determine the relationship between technical implementation of IMD with the incidence of postpartum haemorrhage.This research uses analytic observational design by the cross sectional approach. Independent variable is the technical implementation of the IMD and the dependent variable was the incidence of postpartum haemorrhage. The subject of this study was 30. Data was collecting by a checklist and be analyzed using the Fisher Exact Test. The results show that mothers who carry out technical implementation of the corresponding IMD were 21 people (70%) and who carry out technical implementation of the IMD that does not fit as many as 9 people (30%). While mothers who experience postpartum haemorrhage are 3 people (10%) and did not experience postpartum haemorrhage are 27 people (90%). The fisher exact test show score of ρ value was 0.207. So there is no relationship between the technical implementation of the IMD with the incidence of postpartum haemorrhage. So this result can be used as the basis to give the information for the health workers (midwives) about the importance of prevention of postpartum haemorrhage by remaining obediently carry out the standard APN by IMD and by improving human resources through sustainable education, and joining the training for the health care.